Description lexicographique fondee sur la modification conceptuelle: conception ≪ modifie - modifieur ≫ - Śmigielska, Beata; Grigowicz, Anna (Neophilologica, 2004)
In this work, the authors examine the issue of lexicographic description. They base their considerations on linguistic structures in which one of the elements performs the function of the modifier of the other element, which is thus fulfilling the role of the modified. The main principles of the modifier-modified lexicographic method by W. Banyś were confronted with other two-element concepts: the predicate-argument one and the theme-rheme one. The authors placed considerable emphasis on pointing out the differences and similarities of the compared concepts.